Pacific Islanders Under German Rule : a Study in the Meaning of Colonial Resistance. - Hempenstall, Peter J. (ANU Press, 2016)
This is an important book. It is a reprint of the first detailed study of how Pacific Islanders responded politically and economically to their rulers across the German empire of the Pacific. Under one cover, it captures the variety of interactions between the various German colonial administrations, with their separate approaches, and the leaders and people of Samoa in Polynesia, the major island centre of Pohnpei in Micronesia and the Indigenes of New Guinea. Drawing on anthropology, new Pacific history insights and a range of theoretical works on African and Asian resistance from the 1960s and 1970s, it reveals the complexities of Islander reactions and the nature of protests against German imperial rule. It casts aside old assumptions that colonised peoples always resisted European colonisers. Instead, this book argues convincingly that Islander responses were often intelligent and subtle manipulations of their rulers' agendas, their societies dynamic enough to make their own adjustments to the demands of empire. It does not shy away from major blunders by German colonial administrators, nor from the strategic and tactical mistakes of Islander leaders. At the same time, it raises the profile of several large personalities on both sides of the colonial frontier, including Lauaki Namulau'ulu Mamoe and Wilhelm Solf in Samoa; Henry Nanpei, Georg Fritz and Karl Boeder in Pohnpei; or Governor Albert Hahl and Po Minis from Manus Island in New Guinea.